Potential characterization of yeasts isolated from Kazak artisanal cheese to produce flavoring compounds. Issue 1 (26th December 2017) - Zheng, Xiaoji; Li, Kaixiong; Shi, Xuewei; Ni, Yongqing; Li, Baokun; Zhuge, Bin
Abstract: Cheese is a typical handcrafted fermented food in Kazak minority from the Uighur Autonomy Region in China and Central Asia. Among the microbial community that is responsible for Kazak cheese fermentation, yeasts play important role in flavor formation during ripening. To develop ripening cultures, we isolated 123 yeasts from 25 cheese products in Kazak, and identified 87 isolates by the D1/D2 domain of the large subunit rRNA gene sequence. Pichia kudriavzevii was the dominant yeast in Kazak cheese, followed by Kluyveromyces marxianus and Kluyveromyces lactis . Of these, the ability to exhibit enzyme of dominant isolates and contribution to the typical flavor of cheeses was assessed. Enzyme producing yeast strains were inoculated in Hazak cheese‐like medium and volatile compounds were identified by head space solid phase micro extraction coupled to gas chromatography and mass spectroscopy. Pichia   kudriavzevii N‐X displayed the strongest extracellular proteolytic and activity on skim milk agar and produced a range of aroma compounds (ethanol, ethyl acetate, 3‐methylbutanol, and acetic acid) for Kazak cheese flavor, could be explored as ripening cultures in commercial production of Kazak cheeses. Abstract : Diversity of native yeasts in Kazak artisanal cheese was explored. Protease, lipase, and β‐galactosidase activities of selected yeast strains were assessed. Impact of different enzyme producing yeast strains on volatile compounds was shown. Kluyveromyces lactis (isolate N‐X) and Kluyveromyces marxianus (24‐5) could be applied to manufacture of Kazak cheeses.